Silver Nanoparticles: A Modern Era of Nanotechnology - Amruta Magar; Dr. Vishweshwar Dharashive; Dr. Sameer Shafi; Gangaram Kartale; Sayali Bedare; Vikas Bhosale (Asian Journal of Pharmaceutical Research and Development, 2024)
Recently, Silver nanoparticlesare used for a wide range of applications, such as wastewater treatment, catalytic activity, wound heal targeted drug administration, antibacterial activity, because of their special and adjustable qualities. For the synthesis of silver nanoparticles, A variety of preparation techniques have been used noteworthy strategies include chemical methods, physical synthetic methods, and biological assisted methods. Characterization is carried out using a variety of entirely distinct methods, such as Fourier transform infrared chemical analysis (FTIR), X-ray Diffraction analysis (XRD), Energy-dispersive X-ray spectroscopy (EDX), transmission and scanning microscopy (TEM and SEM), and UV-Vis chemical analysis. This review paper's objective is to discuss the Synthesis, Characterization, Antimicrobial and Anticancer MOA of Silver nanoparticles and their toxicity and future prospectives.